2021
DOI: 10.1017/dmp.2021.236
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Map of Non-Clinical Evidence Syntheses Published Globally on COVID-19

Abstract: Study Objective: Evidence syntheses perform rigorous investigations of the primary literature and they have played a vital role in generating evidence-based recommendations for governments worldwide during the COVID-19 pandemic. However, there has not yet been an attempt to organize them across topic and other characteristics. This study performed a systematic mapping exercise of non-clinical evidence syntheses pertaining to COVID-19. Methods: This study conducted a systematic search on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Concerns about adverse mental health effects of COVID-19 have been raised since the beginning of the pandemic 1 , 2 based on evidence for such outcomes in past infectious disease outbreaks 3 , 4 , 5 and natural disasters. 6 Many empirical papers subsequently investigated the association of the pandemic with mental health, 7 and most concluded that the pandemic caused dramatic increases in anxiety and depression. However, such studies mostly compared online pandemic-era surveys with low or unreported response rates against prepandemic government benchmark probability surveys.…”
Section: Introductionmentioning
confidence: 99%
“…Concerns about adverse mental health effects of COVID-19 have been raised since the beginning of the pandemic 1 , 2 based on evidence for such outcomes in past infectious disease outbreaks 3 , 4 , 5 and natural disasters. 6 Many empirical papers subsequently investigated the association of the pandemic with mental health, 7 and most concluded that the pandemic caused dramatic increases in anxiety and depression. However, such studies mostly compared online pandemic-era surveys with low or unreported response rates against prepandemic government benchmark probability surveys.…”
Section: Introductionmentioning
confidence: 99%